Hubungan Pengetahuan Ibu dengan Interaksi Sosial pada Anak Autism Spectrum Disorder di Unit Pelaksana Teknis Pusat Layanan Disabilitas dan Pendidikan Inklusi Surakarta - Anjelina Tri Jayanti, Sherly; Resina Putri, Anggi (Politeknik Kesehatan Kemenkes Surakarta, 2023)
ABSTRACT Background: Language and speech are one of the parameters of child development. Language and speech are parts of communication that are interrelated and cannot be separated. In practice, the child first develops aspects of his language and then begins to master speaking. Purpose: This study aims to determine the relationship between mother's knowledge about speech language development and social interaction in children with autism spectrum disorder in the technical implementation unit of the Surakarta disability and inclusive education service center. Methods: This research uses quantitative research with a cross-sectional approach, namely taking a relatively short time and a certain place.The data collection technique used a purposive sampling technique with a sample of 30 female respondents. Univariate and bivariate analysis using the Spearman Rank statistical test. Results: In the results of the study it was found that mother's knowledge about speech language development was dominated by the sufficient category (50%) and social interaction in children with autism spectrum disorder was dominated by the poor category (76.7%). The results of the bivariate analysis in this study showed that there was a significant relationship between mother's knowledge about speech language development and social interaction in children with autism spectrum disorder in the technical implementation unit of the Surakarta disability and inclusive education service center with the results of the Spearman rank statistical test showing that the value of p = 0.002 (p ≤ 0.05). Conclusion: There is a relationship between mother's knowledge about speech language development and social interaction in children with autism spectrum disorder. Keywords: Mother's Knowledge, Social Interaction, Autism Spectrum Disorder